The self and autism - Fordham, Michael, 1905-1995 (Library of analytical psychology, 1976)
The Self and Autism is a piece of original research into maturation in infancy and its psychopathology. Michael Fordham was the first to introduce the idea that the self, previously considered realizable only in later life, could be experienced by children in a manner appropriate to their age; he also found that the archetypes of the collective unconscious whose images could be demonstrated in childhood, functioned in essentially the same way as Jung described in the case of adult persons. From these two concepts he developed a theory of individuation in childhood.